Hotel Frontline Employees’ Perceptions about Organizational Variables: Evidence of Mashhad’s Hotels - Fahmideh, Ghazal Adel (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2014)
This study intended to investigate frontline employees’ perceptions of Organizational Citizenship behavior (OCB), Perceived Organizational Support (POS), and Organizational Identification (OI) according to their demographic characteristics: gender, age, and education in the context of hotel industry in Mashhad, Iran. The aim of study is to investigate any differences in the employees’ (OCB) perceptions specifically altruism, courtesy, sportsmanship, civic virtue, conscientiousness, perceived organizational support, and organizational identification in accordance with their age, gender, and education. The population under investigation consists of 127 frontline employees working in Mashhad 5 Star hotels. With the help of SPSS 20 relationships were assessed. The study revealed that frontline employees perceive OI at higher levels than OCB and POS. Generally, older male and highly educated employees perceived these behaviors and attitudes at higher levels than young female employees. Results in details are presented within the study. Keywords: Organizational Citizenship Behavior, Perceived Organizational Support, Organizational Identification, Frontline employees, Demographic Characteristics

Öz: Bu çalışmada İran’da Mashhad şehrindeki otellerde görev yapan ön hat çalışanlarının yaş, cinsiyet ve eğitimsel bağlamda Örgütsel Vatandaşlık Davranışı (ÖVD) algılarını, Algılanan Örgütsel Destek (AÖD) ve Örgütsel Kimlik (ÖK) çerçevesinde incelenmesi amaçlanmıştır. Bu çalışmada çalışanların başkalarını düşünme, nezaket, centilmenlik, medeni erdem, vicdan, örgütsel destek,örgütsel kimlik gibi değişkenlere yönelik yaklaşımları yaş, cinsiyet ve eğitim seviyesine göre araştırılmıştır. Araştırmaya katılanlar Mashhad’daki 5 yıldızlı otel çalışanı olan 127 ön hat personelidir. Veriler SPSS 20 programı kullanılarak incelenmiştir. Çalışmanın bulgularına gore ön hat personeli örgütsel kimlik değişkeninin örgütsel vatandaşlık davranışı ve örgütsel destek değişkenlerine oranla daha önemli olduğunu düşünmektedir. Genel olarak yaşca büyük olan ve eğitim almış personel bu davranışlarla ilgili değişkenleri gençlere oranla daha yüksek olarak değerlendirmişlerdir. Anahtar Kelimeler: Örgütsel Vatandaşlık Davranışı, Algılanan Örgütsel Destek, Örgütsel Kimlik, Ön büro çalışanları, Demografik özellikler.
Master of Science in Tourism Management. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Tourism, 2014. Supervisor: Prof. Dr. Hasan Kılıç.
Keywords: Tourism; Hotel Indistry; Employees; Mashhad (Iran); Human Resource Management; Research; Organizational behavior; Organizational effectiveness; Hotel management and organization; Social aspects; Employee Attitudes (Psychology); Job Satisfaction; Organizational Citizenship Behavior; Perceived Organizational Support; Organizational Identification; Frontline employees; Demographic Characteristics